2006
DOI: 10.1007/s11604-006-0053-y
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the apparent diffusion coefficient in the liver: is it a reliable index for hepatic disease diagnosis?

Abstract: ADC measurement of the left hepatic lobe was far more incorrect than that of the right lobe if cardiac gating was not employed. The administration of Buscopan worsened the image quality of the left lobe and made visual evaluation difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 9 publications
3
49
0
Order By: Relevance
“…Several studies [5][6][7] have suggested that signal loss in DWI and artificially increased ADCs can be observed in the left liver lobe due to cardiac motion. In addition, localized signal loss in DWI of the right liver lobe was recently reported to occur in respiratory triggered DWI, depending on difference of directions of MPGs [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies [5][6][7] have suggested that signal loss in DWI and artificially increased ADCs can be observed in the left liver lobe due to cardiac motion. In addition, localized signal loss in DWI of the right liver lobe was recently reported to occur in respiratory triggered DWI, depending on difference of directions of MPGs [8].…”
Section: Discussionmentioning
confidence: 99%
“…However, signal loss in DWI and artificially elevated ADCs have been reported to occur in the left liver lobe [5][6][7]. A possible explanation for this phenomenon is cardiac motion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A difference may also exist between different anatomical locations. Thus, the ADC measurements in the right liver lobe may be lower than in the left lobe, because of the addition of heart motion (17). Other authors have shown that cardiac motion may affect the signal intensity of both the left and right lobes (18), which may explain why the differences between the two lobes were of no importance in our study.…”
Section: Discussionmentioning
confidence: 60%